The Evolution of HIV Patient Retention and Care in French Guiana: A Broader View From the Système National des Données de Santé - Hélène Duplan; Sébastien Rabier; Christine Sudre; Leila Adriouch; Aude Lucarelli; Florence Huber; Louise Mutricy; Jean Marc Wojcik; Nicolas Vignier; Nicolas Vignier; Etienne Pascolini; Antoine Adenis; et al. (Frontiers Media S.A., 2022)
BackgroundAlthough the simplification of antiretroviral (AVR) treatment regimens and follow-up has led to fewer constraints for patients with HIV, their follow-up remains of paramount importance to optimize AVR therapy, to detect and prevent HIV-related morbidity, and prevent secondary infections. The problem of follow-up interruption in French Guiana has been persistent and seemingly impervious to efforts to alleviate it.ObjectiveThe objective was to follow the trend of follow-up interruptions and to test the hypothesis that an increasing number of patients was, in fact, followed by private practitioners.MethodUsing the complementary lenses of the hospital HIV cohort and the health insurance information system, we looked at the incidence of follow-up interruption and the proportion of patients followed by private practitioners.ResultsWe tallied 803 persons that were not known to have died and who were lost to follow-up. Over time, hospital outpatients were lost to follow-up significantly sooner. By contrast, there was a significant trend with more and more patients exclusively followed by private practitioners.ConclusionWhile hospital outpatient care remains by far the most common mode of patient care, there seems to be a gradual erosion of this model in favor of private practice.